Students’ Perception on Rewriting Task on Syntax Course - Ihsan, M. Muadz Muwaffaq; Muhayyang, Maemuna; Korompot, Chairil Anwar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study aims to explore students’ perceptions of the rewriting task in the syntax course. The researcher applied the descriptive-qualitative method to achieve the objective of the research. The data were collected by conducting interviews. The subjects of the research were 10 students who had enrolled in the Syntax course at the State University of Makassar. The subjects were chosen using a simple random technique. Based on the result of the study, the students’ perceptions suggest that the rewriting task in the Syntax course is helpful, assisting students to understand the material, but ineffective. Based on the findings, the conclusion is that the student’s perceptions are mostly positive regarding the rewriting task in the syntax course. Although this task is well-designed by the lecture and is mostly perceived positively by students, there are also students who perceive it negatively.